STUDIES ON IMPACT OF TRAINING PROGRAMMES ON LEVEL OF ADOPTION OF IMPROVED PRACTICES AMONG FISH FARMERS OF NORTH BIHAR - DUBEY, PUSHPA; MISHRA, RANJEET KUMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2015)
The study was conducted in four blocks of Kosi region of North Bihar during 2013-14 to find out the adoption behaviour of fish farmers. Thirty trained and thirty untrained fish farmers were interviewed personally with the help of pre-tested interview schedule. The study reveals that pond preparation techniques viz, pond cleaning and drying, repair and maintenance of pond bundh, control of aquatic weed, removal of wild fish by fish toxicant were fully adopted by 14, 12, 11, 11, 11 farmers, respectively among thirty trained fish farmers. Trained fish farmers look precaution measures against fish diseases. There was significant difference between trained and untrained groups in respect to level of adoption of improved fish farming, Z value 4.86 Significant at 1% level of probability.